(3eONd dEOGQI GdCYeGd (B/ s - (3HbGT, TgjQIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2015)
(3eaGgje CSGSjI Mhd GOGQI GdGYeGd , JWhQ GdacQ GdGOGQj ,GdJfXje hGdgjcd GdJfXjej ,YedjI GJNGP GdbQGQ , GdJNWjW, GdJMajR, GdbjGOI hGdQbGHIs
(3eQGLY U(B.105s
Keywords: (3GJNGP GdbQGQGJs; (3GOGQI GdGYeGds; (3GdJNWjWs; (3GdQbGHIs